Minimum Isoseismal Distribution Based On Macroseismic Interpolation For Earthquake Disaster Mitigation in Palu City - Telly Kurniawan; Bambang Sunardi; Supriyanto Rohadi; Yusuf Hadi Perdana; Tio Azhar Prakoso Setiadi (Universitas Gadjah Mada, 2019)
Palu City is the city that suffered the most damage and many casualties, effect from event Palu-Donggala earthquake on September 28, 2018. This earthquake triggered a tsunami, liquifaction and landslides which caused difficulties in determining a closest safe location for the temporary evacuation site in location affected disaster. The aftershocks that occurred after the main earthquake caused unrest for refugees and village government officials, because it was feared that the location to be used as a temporary evacuation site would run into the impact of an earthquake similar to other severe locations. To determine a safe location around the impact area destructive earthquake, information about the map of the minimum isoseismal distribution is very important. This study aims to map Minimum Isoseismal Distribution as the place that has the smallest disaster risk in areas affected by the earthquake, tsunami, liquefaction and landslides. The research methodology that be done are plotting and interpolate data from macroseismic surveys then were verified using satellite citra data and photo documentation of survey. The results showed that a minimum isoseismal distribution was found in 8 areas, located in the village: Kabonena, Lere, Kamonji, Siranindi, between Boyaoge and Nunu, Tawanjuka, Palupi and Tinggede.